KOORDINASI ANTARA KEPOLISIAN NEGARA REPUBLIK INDONESIA DENGAN APARAT PENGAWAS INTERNAL PEMERINTAH DALAM PENYELIDIKAN TINDAK PIDANA KORUPSI DANA DESA - Awi Ramadani; Otong Rosadi (Programa Magister Ilmu Hukum Universitas Ekasakti, 2022)
Article 385 of Law Number 23 of 2014 concerning Regional Government adheres to the norm that the Government's Internal Supervisory Apparatus is obliged to conduct an examination of alleged irregularities that are reported by the public. This research is a legal research with a descriptive analytical specification. The form of coordination between the Indonesian National Police and the Government's Internal Supervisory Apparatus in the Investigation of Corruption Crimes of Village Funds in the Legal Territory of the Pesisir Selatan Police is in the form of horizontal coordination. Coordination was carried out in 2019 there were 2 (two) investigations, in 2020 there was 1 (one) investigation regarding alleged criminal acts of corruption in the village funds of the South Gurun Panjang, Kec. Shadow. Furthermore, in 2021 there will be 1 (one) investigation regarding the alleged criminal act of misappropriation of village funds in Nagari Nanggalo Koto XI Tarusan. Coordination is carried out to examine documents related to state finances, namely village funds that are suspected of being misappropriated. The coordination carried out by the Pesisir Selatan Police with APIP has been carried out so far by telephone, Discussion, Exposure (Degree of Cases) which includes APIP. Obstacles in Coordination Between the Indonesian National Police and the Government's Internal Supervisory Apparatus in Investigating the Crime of Village Fund Corruption in the Legal Territory of the Pesisir Selatan Police is when the APIP states that the act was only an administrative error and then he pays compensation for the amount of money that is claimed for the loss, then law enforcement will discontinued. The role of APIP is only â€œunderstoodâ€ through various Memorandums of Understanding. On the other hand, the independence and competence of APIP is also a separate obstacle.